Konsep Peningkatan Kompetensi Widyaiswara dalam Penyusunan Karya Tulis Ilmiah Indonesia dengan Model Pembelajaran 70-20-10 - Agus Suharsono (Jurnal Kewidyaiswaraan, 2020)
This paper discusses the development of the implementation of one of the DPP IWI Work Programs for the 2019-2023 period, namely the development of the Widyaiswara profession through the holding of conferences, seminars, scientific meetings, community service, and providing consultancy and assistance with books or scientific journals. The method used is level one development that is researching but not proceeding with making products and not conducting field testing. Widyaiswara profession with the main material about making papers in the field of education. Requirement Analysis, Design, its implementation is carried out between the DPP IWI and LAN as a guiding institution. Using the 70-20-10 blended learning model by utilizing the LAN website or the DPP IWI website, couching, guidance, Community Practices, and integrated action learning in the workplace to submit to accredited journals or exhibited at Widyaiswara’s Annual Scientific meetings that try to go hand in hand with the Widyaiswara Annual Congress. This model can be used as a learning model in ASN Corporate University.